ENVIRONMENTALLY SUSTAINABLE INVENTORY MODEL UNDER PERMISSIBLE DELAY IN PAYMENTS - Ritha, W.; Vinoline, I. Antonitte (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Within the economic order quantity (EOQ) framework, the main purpose of this paper is to investigate the supplier optimal replenishment policy of permissible delay in payments. All previously published articles dealing with optimal order quantity with permissible delay in payments assumed that the supplier only offers the retailer fully permissible delay in payments if the retailer ordered a sufficient quantity. Otherwise, permissible delay in payments would not be permitted. However, in this paper, we want to extend this extreme case by developing the mathematical model for determining the cycle time. Under this condition, we model the retailers inventory system as a cost minimization problem to determine the retailers optimal inventory cycle time and optimal order quantity. Finally, numerical examples are given to illustrate all these cases and to draw managerial insights.